Population genetic structure of the blue swimming crab (Portunus pelagicus) along the Andaman Sea Coast of Thailand - Juthamas Suppapan,; Apirak Songrak,; Worawitoo Meesook,; Verakiat Supmee, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The blue swimming crab (Portunus pelagicus) is a valuable commercial species. In Thailand, the consumption of the blue swimming crab is increasing. To construct an effective sustainable management plan, genetic information is required. Knowledge of natural stock genetic information can help policymakers design fishing and conservation management policies to maintain genetic diversity. In our study, we examined the genetic structure of the blue swimming crab population on the Andaman Sea coast of Thailand. Partial sequences of the mitochondrial DNA control region (mtDNA CR) with a size of 369-371 base pairs were studied in 150 individuals collected from five sampling sites along Thailand’s Andaman Sea coast. Seventy-one haplotypes were characterized by 127 polymorphic sites, indicating high haplotype diversity but low nucleotide diversity across five localities. The multiple tests of population genetic analysis showed a lack of genetic structure. The absence of genetic structure was possibly caused by a high level of gene flow due to the larval blue swimming crab’s high dispersal ability. Demographic history findings indicate that the blue swimming crab population has expanded. The findings of our study can be used to guide the management of the blue swimming crab in this region of the Andaman Sea to conserve genetic diversity.